Fire Has a Positive Effect on the Abundance of Sun Spiders (Arachnida: Solifugae) in the Cerrado-Pantanal Ecotone - Bruno Arguelho Arrua; Leonardo Sousa Carvalho; Thiago Silva Teles; Maxwell da Rosa Oliveira; Danilo Bandini Ribeiro (Fire, 2023)
Fire is an important disturbance factor in shrublands, grasslands, and savannas. It alters the habitat of a multitude of species and, under natural dynamics, is a major determinant of landscape vegetation patterns. Here, we evaluate the effects of different wildfire regimes on the abundance of sun spiders in the Cerrado-Pantanal ecotone. To study how different fire regimes affect the number of individual sun spiders, we considered the frequency of fire occurrences in the last 20 years and classified locations as high frequency or low frequency. We also classified the time of the last fire in 2020 as occurring in the first or second half of the year. In addition, we compared the number of individual sun spiders before and after fire. We found no effects of fire frequency and period when the fire occurred in 2020, but the number of individual sun spiders was higher after wildfires. Although ground-dwelling are considered fire sensitive, some can employ strategies to tolerate fire so that they are able to not only survive, but also reproduce in fire-prone landscapes. Thus, we suggest that sun spiders are resilient, can explore sites under different fire regimes, and can be considered pyrophilous species.